Idealizing a Dichotomy between Islam and Sharī‘ah: the Orientalist and Missiological Stereotype - Abdulazeez Muhammad Ashimiyu (International Journal of Islamic Khazanah, 2022)
Contacts between civilizations and the struggle for domination are parts of human historical facts. Religion is regardedas a major denominator in tracing the cultural and traditional identity of a given community. Objective accounts of these contacts establish the tendency of collaborative orientalists and missiological prejudices separating Islam from Sharia through treatises and media misrepresentations. This study employed a qualitative approach by applying analytical and descriptive method s . Th e d ata were collected from documentary evidence and literary works. Shara was identified by examining ideological prejudices and constructs that opposedIslam and its law. Both enthusiasts and rejectionists of orientalism and missionary evangelism have revealedthat the good image of Islam and Shar a is a consistent target;hence it is distorted. It is submitted that hate authorship should be discountenanced to create harmonious and peaceful co-existence among major faith-based adherents.